2023
DOI: 10.3390/healthcare11192627
|View full text |Cite
|
Sign up to set email alerts
|

Health Providers’ Response to Female Adolescent Survivors of Sexual and Gender-Based Violence and Demand Side Barriers in the Utilization of Support Services in Urban Low-Income Communities of Nigeria

Olutoyin Opeyemi Ikuteyijo,
Andrea Kaiser-Grolimund,
Michael D. Fetters
et al.

Abstract: Survivors of sexual and gender-based violence (SGBV) are often hindered in their quest to access quality healthcare. This has a significant effect towards the achievement of Sustainable Development Goal SDG Target 3.7. to ensure universal access to sexual and reproductive healthcare services. This study is focused on identifying some of the demand side barriers in accessing health care services, particularly among young girls who are survivors of SGBV within intimate relationships in poor urban areas in Nigeri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…This study found that gender-specific experiences, such as gender-based violence (GBV), can have a negative impact on adolescents' health literacy. Because of fear, shame, or a lack of support, girls who have experienced gender-based violence or stigma are more likely to be hesitant to seek health information or care (Ikuteyijo et al, 2023). This can result in a lack of knowledge about available health services and resources.…”
Section: Gender-based Violencementioning
confidence: 99%
See 1 more Smart Citation
“…This study found that gender-specific experiences, such as gender-based violence (GBV), can have a negative impact on adolescents' health literacy. Because of fear, shame, or a lack of support, girls who have experienced gender-based violence or stigma are more likely to be hesitant to seek health information or care (Ikuteyijo et al, 2023). This can result in a lack of knowledge about available health services and resources.…”
Section: Gender-based Violencementioning
confidence: 99%
“…Young people may be hesitant to seek healthcare services, including health education materials, due to stigma, discrimination, and fear of judgment (World Bank, 2022;Francis & DePalma, 2014). This reluctance can lead to delayed care (Stavropoulou, 2019), missed preventive measures (Ikuteyijo et al, 2023), and poorer health outcomes (Sumbane & Makua, 2023), all of which can be linked to lower health literacy.…”
Section: Stigmatizationmentioning
confidence: 99%